2021
DOI: 10.1111/ijac.13979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of expanded vermiculite on the properties of fired bricks from water treatment sludge

Abstract: In the present study, the suitability of using water treatment sludge (WTS) as the main raw material and expanded vermiculite (EV) as aggregate in the production of fired bricks was investigated. Mixtures containing between 75%-100% WTS by weight (wt.) and 5%-25% EV by wt. were prepared at various proportions. The mixtures were compressed under 40 MPa pressure and fired at 1000 • C. It was found the incorporation of EV in fired bricks resulted in a decrease in thermal conductivity, compressive strength, and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…However, the current study has confirmed that care must be taken when using WTS as partial replacement in clay‐based refractories as it contains impurities that lower the mullitization temperature and form a liquid phase with relatively low viscosity in the Al 2 O 3 –SiO 2 system 27 . Various studies using WTS as a partial replacement of clay minerals in the production of clay bricks show that increasing WTS content in clay mixtures increased porosity and water absorption and a decrease in bulk density 43 . It is reported that a replacement of up to 30 wt.% WTS in fired clay gives a good combination of properties for brick production.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…However, the current study has confirmed that care must be taken when using WTS as partial replacement in clay‐based refractories as it contains impurities that lower the mullitization temperature and form a liquid phase with relatively low viscosity in the Al 2 O 3 –SiO 2 system 27 . Various studies using WTS as a partial replacement of clay minerals in the production of clay bricks show that increasing WTS content in clay mixtures increased porosity and water absorption and a decrease in bulk density 43 . It is reported that a replacement of up to 30 wt.% WTS in fired clay gives a good combination of properties for brick production.…”
Section: Resultssupporting
confidence: 64%
“…27 Various studies using WTS as a partial replacement of clay minerals in the production of clay bricks show that increasing WTS content in clay mixtures increased porosity and water absorption and a decrease in bulk density. 43 It is reported that a replacement of up to 30 wt.% WTS in fired clay gives a good combination of properties for brick production. However, the sintering temperature can be increased to achieve higher density and lower porosity.…”
Section: Influence Of Composition On the Properties Of Refractory Bricksmentioning
confidence: 99%